Editorial Articles in Honour of Alister McGrath - Jain, Ravi Scott (2023)
An introduction is presented in which the editor discusses articles in the issue on topics including the motivation and collaborative work of Alister McGrath in theology, the comparison between technological and Christian immortality and the abductive nature of science and theology.
Keywords: ALISTER McGrath; Christianity; DOCTRINAL theology